PENGEMBANGAN GAME JEGOG BERBASIS ANDROID - I Gede Wija Antara; I Gede Mahendra Darmawiguna; I Made Gede Sunarya (Universitas Pendidikan Ganesha, 2014)
Gamelan Jegog is one of thetraditional instrument which originally comesfrom Bali. Each Jegog’s instrument consists ofeight piece of bamboo with each piece is called as